Exenatide with Metformin Ameliorated Visceral Adiposity and Insulin Resistance - Xuan Du; Wen Lu; Zijun Lu; Xinyu Shao; Chunhong Hu; Bimin Shi (Journal of Diabetes Research)
Background. To study the effectiveness of exenatide with metformin and sequential treatment with exenatide and glargine added to metformin and their influence on insulin sensitivity and adipose distribution. Methods. 20 newly diagnosed obese type 2 diabetic patients were enrolled, and 2-month washout treatment of metformin, 6-month exenatide treatment, and 6-month glargine treatment were administrated sequentially accompanied with previous metformin. Glucolipid metabolic parameters were compared among groups. Adipose distribution was quantified with computerized tomography according to anatomy, dividing into visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT), adding up to total adipose tissue (TAT). Results. The 6-month exenatide treatment dramatically ameliorated the glucose and lipid profile, improved insulin sensitivity, and mainly decreased VAT and also the ratio of VAT/SAT (RVS). The following 6-month glargine treatment increased VAT. The whole 12-month sequential treatment with exenatide and glargine added to metformin basically improved the insulin sensitivity and glucolipid control though VAT rebounded at the end, however without deteriorating the other parameters. Conclusion. Exenatide is an ideal treatment for obese type 2 diabetic patients in the aspect of adipose tissue distribution. Sequential treatment of exenatide and glargine could be an alternative for low-income patients who cannot afford GLP-1 agonist for long time. This trial is registered with ChiCTR-OOC-17013679.